Gambaran Pola Jajan, Frekuensi Menyikat Gigi dan Status Karies Gigi Anak Usia 11-12 Tahun di Sd Negeri Gumpang 01 Kecamatan Kartasura Kabupaten Sukoharjo - Safitri, Dian Ayu Rahmania; , drg. Ana Riolina, MPH; , drg. Retno Sari (2015)
Dental caries was type of teeth disease that attacked hard tissues (enamel, dentin, cementum), caused by microorganism activities of carbohydrate fermentation. Children were generally have high risk on caries, because of their snacking pattern. Cleaning teeth behavior can also become the factor of caries. Technique, time, and frequency of toothbrushing can affect oral cavity hygiene. This was observational study with cross sectional approach. The study was aimed to find out the description of snacking pattern, toothbrushing frequency, and caries status of 11-12 year old students of SDN Gumpang 01, Kartasura, Sukoharjo. 61 of sixth grade students were registered as study sample as total sampling applied. The data of caries status was gained by DMF-T, and questionnaire were applied to understand snacking pattern and toothbrushing frequency. The result showed that the highest snack pattern of students were snack and candy/chocolate, bought 2-3 times a day. Toothbrushing was done 2-3 times a day on the morning and evening bath time. The average of DMF-T score of the students showed very low category, 0.98 which indicate that the student have at least one tooth with caries.